SEMA3C drives cancer growth by transactivating multiple receptor tyrosine kinases via Plexin B1 - James W Peacock; Ario Takeuchi; Norihiro Hayashi; Liangliang Liu; Kevin J Tam; Nader Al Nakouzi; Nastaran Khazamipour; Tabitha Tombe; Takashi Dejima; Kevin CK Lee; Masaki Shiota; Daksh Thaper; et al. (EMBO Molecular Medicine)
Abstract Growth factor receptor tyrosine kinase (RTK) pathway activation is a key mechanism for mediating cancer growth, survival, and treatment resistance. Cognate ligands play crucial roles in autocrine or paracrine stimulation of these RTK pathways. Here, we show SEMA3C drives activation of multiple RTKs including EGFR, ErbB2, and MET in a cognate ligand‐independent manner via Plexin B1. SEMA3C expression levels increase in castration‐resistant prostate cancer (CRPC), where it functions to promote cancer cell growth and resistance to androgen receptor pathway inhibition. SEMA3C inhibition delays CRPC and enzalutamide‐resistant progression. Plexin B1 sema domain‐containing:Fc fusion proteins suppress RTK signaling and cell growth and inhibit CRPC progression of LNCaP xenografts post‐castration in vivo. SEMA3C inhibition represents a novel therapeutic strategy for treatment of advanced prostate cancer.